Vertical Integration and Supplier Finance - Holger Görg; Erasmus Kersting (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We investigate the financial implications of a multinational firm's choice between outsourcing and integration from the perspective of the supplier. Using a simple model, we explore the extent to which an integrated supplier's access to finance, as well as its sources of funding, change relative to a firm supplying a multinational at arm's-length. The model predicts that integrated firms have better access to finance and cover a larger share of their costs using internal funds. Furthermore, improvements in a host country's level of financial development have less of an impact on the financial situation of integrated suppliers. We present empirical evidence from firm-level data for over 60 countries broadly supporting the predictions.
Keywords: F23; G32; F20; 330